Analysis of Accreditation's Impact on Student Numbers in South Sumatra Private Universities Using K-Means Clustering - Muhammad Sulkhan Nurfatih; Yusi Nurmalasari; Agustian Prakarsyah (Media Journal of General Computer Science, 2024)
Private universities in Indonesia are essential in meeting the educational needs of the country's increasing number of students. Among the key determinants of student enrollment is the accreditation status of these institutions. This study investigates how accreditation status influences student numbers at private universities in South Sumatra, employing the K-Means clustering method for analysis. Data from various institutions across South Sumatra were collected and analyzed, revealing distinct patterns in how universities are grouped based on their accreditation and enrollment figures. The findings shed light on the significant relationship between accreditation status and student enrollment, offering valuable insights for policymakers and university administrators. These insights can inform the development of effective student admission strategies, ultimately contributing to the growth and success of private universities in the region. This research not only highlights the importance of accreditation but also provides a comprehensive understanding of the factors driving student growth at private universities in South Sumatra.